Plan de negocios para la producción y comercialización de un suplemento vitamínico para personas que padecen diabetes en el Ecuador - Jarrín Beltrán, Juan José (2020)
The presentation of the business plan focuses on determining the commercial, operational and financial viability of undertaking an organization in charge of producing and marketing a specialized vitamin supplement in people with diabetes. The name chosen for the supplement is DiabPower that transmits a message associated with the essence of the product that is to strengthen the defenses of diabetics, which are reduced due to the special diet they must carry to keep glucose levels and carbohydrate consumption controlled. DiabPower has a composition of minerals such as zinc, magnesium and chromium that allows the best assimilation of nutrients in the body; Vitamins B, C and D increase consumer defenses. The distribution channel for marketing the product are the main pharmacies such as Fybeca, Sana Sana, Cruz Azul, Pharmacys, Economic Pharmacies and Medicity, as a support for the distribution channel a promotion plan is established with the medical professionals who prescribe this type of vitamin supplements. In the financial aspect the company requires an initial investment of 130,779 dollars that will be contributed by the shareholders in 70 percent and the balance of 30 percent is financed by a five-year bank loan. The financial valuation allows you to recommend the start-up of the company, because the shareholders recover their initial investment and obtain a return higher than the opportunity cost.